Profil Keterampilan Proses Sains (KPS) Mahasiswa Fisika pada Materi Listrik Magnet - Yolanda, Yaspin (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2019)
This study describes the profile of the science process skills (KPS) of STKIP PGRI Lubuklinggau students on magnetic electric material. The subjects of the research were the third semester students who took magnet electricity courses. Sampling was done by purposive sampling. The research method used was Qualitative Positive Descriptive Method. Data were analyzed qualitatively and quantitatively using an instrument in the form of a KPS diagnosis test. Based on the results of KPS research on student electricity magnet on the subject of Electric magnet, it can be concluded that (1) The skills of the science process of magnet electricity are skilled, and (2) The solution to solve the problem of availability of KPS aspects is to train and be trained with the KPS approach to magnetized student electricity so that the availability of KPS aspects can appear / available. The average percentage increase in KPS are, 82% observation skills, 80% classification skills, 85% interpretation skills, 78% prediction skills, 88% experimental planning or investigation skills, 87% skills using tools and materials, 80% skills in applying concepts or principles %, 85% communication skills, 84 question asking skills, and 79% hypothesized skills. The research findings indicate that there is a significant increase in 82.8%.